(untitled) (Journal of Hama University, 2022)
The effect of foliar spraying with dry yeast extract at concentrations (15 and 20 g/l) and ascorbic acid at concentrations of (400, 600 ppm) and their interactions were studied: yeast (15 g/l) + ascorbic acid (400 ppm) and yeast (20 g/l) + ascorbic acid (400 ppm) in some chemical, quality and productive characteristics of the (Coscia) pear fruits during the 2020 season, in Al-Sefira district of Aleppo Governorate, where the spraying was carried out in the yield mature, while the control was left without treatment. The results showed that the combined foliar spraying with yeast and ascorbic with both concentrations improved the, quality and productive properties with significant differences compared to the control, as it reached the highest production in treating the extract Yeast at a concentration of (20 g/l) + ascorbic acid (400 ppm) (51.55 kg/tree) followed by co-fertilization with yeast (15 g/l) + ascorbic (400 ppm), which reached (48.20 kg/tree) compared to the control (30.35). Kg/tree). The average weight of the fruit increased, reaching (133.86 ، 128.64g) respectively compared to the control, (82.92g). The spray treatment surpassed the yeast extract at a concentration of (20g/l) + ascorbic acid (400 ppm) in increasing the average size of the fruit. It reached (171 cm3) compared to the control (84 cm3). The results also showed that the foliar spraying with yeast and ascorbic acid at different concentrations increased the percentage of total soluble solid (TSS) with significant differences compared with the control, the highest of which was yeast (20 g/l) + ascorbic (400 ppm) (12.87%) and the control reached (10.23%).The highest pH value was by at-fertilization with yeast (20 g/l) + ascorbic (400 ppm), reaching (4.68) compared to (3.58). The percentage of vitamin C was increased by the combined treatment of yeast and ascorbic acid in both concentrations and the treatment of ascorbic acid (600 ppm), reaching (14.88 mg / 100 ml) on the control (8.5 mg / 100 ml).